Bis-pyridylethenyl benzene as novel backbone for amyloid-β binding compounds. Issue 23 (1st December 2016) - Nabuurs, Rob J.A.; Kapoerchan, Varsha V.; Metaxas, Athanasios; Hafith, Sarah; de Backer, Maaike; Welling, Mick M.; Jiskoot, Wim; van den Nieuwendijk, Adrianus M.C.H.; Windhorst, Albert D.; Overkleeft, Herman S.; van Buchem, Mark A.; Overhand, Mark; et al.
Graphical abstract: Abstract: Detection of cerebral β-amyloid (Aβ) by targeted contrast agents is of great interest for in vivo diagnosis of Alzheimer's disease (AD). Partly because of their planar structure several bis-styrylbenzenes have been previously reported as potential Aβ imaging agents. However, these compounds are relatively hydrophobic, which likely limits their in vivo potential. Based on their structures, we hypothesized that less hydrophobic bis-pyridylethenylbenzenes may also label amyloid. We synthesized several bis-pyridylethenylbenzenes and tested whether these compounds indeed display improved solubility and lower Log P values, and studied their fluorescent properties and Aβ binding characteristics. Bis-pyridylethenylbenzenes showed a clear affinity for Aβ plaques on both human and murine AD brain sections. Competitive binding experiments suggested a different binding site than Chrysamine G, a well-known stain for amyloid. With a Log P value between 3 and 5, most bis-pyridylethenylbenzenes were able to enter the brain and label murine amyloid in vivo with the bis(4-pyridylethenyl)benzenes showing the most favorable characteristics. In conclusion, the presented results suggest that bis-pyridylethenylbenzene may serve as a novel backbone for amyloid imaging agents.